Análise e avaliação da demanda e da disponibilidade hídrica nos alto e médio curso do Rio Uberabinha e o abastecimento público em Uberlândia (MG) - Queiroz, Arlei Teodoro de (2012)
The understanding of the phases within the hydrological cycle is essential for hydrological studies, being utilized as a territorial unit for conducting such studies, watershed related. In this sense, this work´s objective is to analyze and evaluate the demand and the availability of surface water in the Uberabinha River Watershed, upstream of the confluence with the Bom Jardim River, located in urban area of Uberlândia, this area which is inserted in the municipalities of Uberlândia and Uberaba; and use hydrology applied techniques to examine in particular two phases of the hydrological cycle, flow and precipitation. For this study we used flow and precipitation data of the Fazenda Letreiro fluviometric and rainfall stations, provided by Agência Nacional de Águas (ANA), located in geographic coordinates of latitude 18°59\'18\"S and longitude 48°11\'25\"W. Beyond these stations five other were used to assist in the confirmation of information. From this data, we performed a preliminary analysis of total rainfall, mean, and extreme precipitation and flow. Continuing with the methodology, a geostatistical analysis of rainfall and flow data was also accomplished, calculating descriptive statistics and probability distribution of Gumbel extreme data. Furthermore, to calculate the current water demand, the number of grants and their respective amounts within the area was listed out, according to information from the Instituto Mineiro de Gestão das Águas (IGAM). As a result, we highlighted the descriptive statistics and graphics of the payback period of maximum rainfall, of the number of consecutive days without rain and without significant rain, and of the minimum and maximum annual flow. The data for the preparation of graphing an intensity-duration-frequency graph of these rainfall events was calculated from the annual maximum rainfall. Also, the hydrograph and the curve of stay from the analyzed period in was prepared from the same data. The study and granting areas were then spatialized in maps; more specifically, the computed monthly amount awarded. From the results obtained, it can be concluded that a collective planning is necessary in the study area, since water availability is insufficient to meet the current demand. The participation of all the users of the watershed is essential for its management and related activities. Such participation should exceed the execution of technical actions, such as being familiar the relationship between land use and flow. Furthermore, the installation and monitoring of a new network of hydrometric and rainfall stations and a study of the technical feasibility of the social and environmental aspects of the implementation of a dam to regularize the flow in the area. Principally, the main use of water in the area of study is the city of Uberlândia s public water supply, therefore, it is suggested that actions be implemented and aimed towards the better utilization of water in the urban environment.